MAGNETIC RESONANCE IMAGING IN THE STUDY OF SCHIZOPHRENIA - Salgado-Pineda, Pilar; Vendrell, Pere (Anales de Psicología / Annals of Psychology, 2004)
The magnetic resonance has had an extensive application in the file of schizophrenia to investigate its neuroanatomical and neurofunctional bases. The structural studies have evolved from the semiautomatic measurements of isolate structures until the sophisticated techniques of automatic analysis using the so called voxel-based morphometry. At the moment, there are several confluent evidences on the existence of diverse structural anomalies that mainly involve the thalamus, the hippocampus, the anterior cingulate region, in addition to parietal and temporal cortical regions. The structural impairment has a left predominance. The technique of functional magnetic resonance (fMRI) has provided evidence on the anomalies of cerebral activation. In the neuropsychological tasks that the patients perform poorer, the pattern observed was cerebral hipoactivity. On the contrary, when the performance of patients is similar to that of the controls hyperactivity patterns are observed that can be interpreted as a compensatory mechanism. The diffusion techniques have allowed detecting white matter anomalies that indicate alterations in the cerebral connectivity. In summary, the magnetic resonance is anon-invasive technique off relative easy use that has facilitated the investigation of the psychobiological bases of schizophrenia and it has opened an enormous potential in the neuroscience research of the most important psychiatric illness.